2010 IEEE International Conference on Communications 2010
DOI: 10.1109/icc.2010.5502074
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Carrier Distributed WDM Ring Network Based on Reconfigurable Optical Drop-Add-Drop Multiplexers and Carrier Wavelength Reuse

Abstract: This paper presents and experimentally demonstrates a multi-carrier distributed wavelength-divisionmultiplexing (WDM) ring network based on reconfigurable optical "drop-add-drop" multiplexers for regional and metro network applications. In the "drop-add-drop" network, optical carriers generated by a centralized multi-carrier light source (MCLS) are "dropped" at the source nodes and used for uplink transmission. Data are "added" to the network by external modulation of one or more carriers. Data are then "dropp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Furthermore, it was reported that the WRMD network is superior to the conventional network in terms of network cost and power consumption on ring topologies in [2]. An example of the WRMD network with mesh topology, as shown in Fig.…”
Section: Wavelength-reusable Multi-carrier-distributed Networkmentioning
confidence: 98%
See 2 more Smart Citations
“…Furthermore, it was reported that the WRMD network is superior to the conventional network in terms of network cost and power consumption on ring topologies in [2]. An example of the WRMD network with mesh topology, as shown in Fig.…”
Section: Wavelength-reusable Multi-carrier-distributed Networkmentioning
confidence: 98%
“…For cost-effectiveness analysis [2], the cost of the single LD, C LD , is defined to equal c cost units. The costs of the WSS, all-optical carrier extraction (ACE), and MLCS are defined as C WSS , C ACE , and C MCLS , respectively.…”
Section: Carrier Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, if the number of wavelengths is increased to increase data transmission capacity, we need to add and control more distributed LDs in the conventional WDM network. This increases the cost, power consumption, and control complexity of the network [2]. Our cost analysis presented in Appendix A, which is an extension of the cost analysis in [2], observes that the WRMD network has lower cost than the conventional WDM network if some condition is satisfied.…”
Section: Introductionmentioning
confidence: 95%
“…Moreover, these filter characteristics require a narrower channel bandwidth and tighter channel spacing. Cascading the filter components in a network narrows the filter bandwidth characteristics after each access node transit, resulting in considerable degradation of the transmission performance [2,3]. In other words, the transmission performance will be drastically degraded if the optical carrier generated by a local light source is slightly detuned because of the tuning error of the light source.…”
Section: Introductionmentioning
confidence: 98%